2020
DOI: 10.1037/pro0000283
|View full text |Cite
|
Sign up to set email alerts
|

I don't believe in miracles: Using the ecological validity model to adapt the miracle question to match the client’s cultural preferences and characteristics.

Abstract: The Miracle Question (MQ) is a characteristic feature of solution-focused brief therapy (SFBT). However, there are times when the terminology of the Miracle Question may not fit the worldview of the client. The main objective of this article is to systematically review the various ways the MQ was adapted and the process of adaptation followed by therapists. The systematic review yielded 24 articles that showed the various ways of adapting the MQ substituting “miracle” with following words/phrases: a fresh star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A miracle question that is not adapted to the client's preferences and characteristics could break the therapeutic alliance. In support of this interpretation, Kayrouz and Hansen (2020) found that some clients had difficulty with the term "miracle but could answer by saying they do not believe in miracles, so they struggled to answer it. The miracle question and religious/spiritual orientations may also conflict (Özkapu, 2022).…”
Section: Techniquesmentioning
confidence: 98%
See 2 more Smart Citations
“…A miracle question that is not adapted to the client's preferences and characteristics could break the therapeutic alliance. In support of this interpretation, Kayrouz and Hansen (2020) found that some clients had difficulty with the term "miracle but could answer by saying they do not believe in miracles, so they struggled to answer it. The miracle question and religious/spiritual orientations may also conflict (Özkapu, 2022).…”
Section: Techniquesmentioning
confidence: 98%
“…This flexible perspective also provides an important resource regarding the religious/spiritual field. Various studies have evaluated basic SFBT techniques from a spirituality perspective as well as spiritual SFBT models that include religious/spiritual-oriented techniques (Crockett and Prosek, 2013;Rassoul, 2016;Kayrouz and Hansen, 2020;Santich, 2020). The following section evaluates some of these common techniques in SFBT in terms of approach and spirituality.…”
Section: Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Viewing contributing factors to their problems as able to “disappear” to reveal a preferred future could even be experienced as therapeutically violent, particularly regarding experiences of racism and discrimination. As a result, the miracle question, which is an intervention used to explore clients’ hidden resources or solutions for their present problems, appeared to offend some of my clients and caused a disruption in therapy (Kayrouz & Hansen, 2020). This possibility was not presented in any of the educational and resource material about SFBT I had accessed.…”
Section: Illustrating a Disjuncture Of Theory And Practicementioning
confidence: 99%